Multifractal Features of Particle-Size Distribution and Their Relationships With Soil Erosion Resistance Under Different Vegetation Types in Debris Flow Basin - Li, Songyang; Gao, Ruoyun; Huang, Maowei; Yang, Liusheng; Yu, Hang; Yu, Chenhui; Tian, Xue; Li, Jian; Lin, Yongming (Frontiers in Earth Science, 2022)
Understanding the influences of different vegetation types on soil particle-size distribution (PSD) is essential to evaluate the effects of sediment control by vegetation restoration in debris flow basin. We studied the effects of different vegetation types on soil PSD in Jiangjiagou gully, Yunnan province, China. We conducted an observational study with 4 vegetation types including bare land, meadow, shrub, and forest. We sampled 5 soil layers including 0~10cm, 10~20cm, 20~30cm, 30~40cm, and 40~50cm, with 3 replicates in each vegetation type. In total, 60 soil samples were collected and analyzed for soil particle size distribution using the laser diffraction method. Fractal theory was used to calculate multifractal parameters. Vegetation types have significant impact on the PSD. The volume fraction of silt particles in shrub and forest is significantly larger than that in bare land, meadow, whereas the total volume fraction of sand particles in bare land and meadow is significantly larger than shrub and forest. The soil depth has no significant effect on soil particle size distribution. The volumetric fractal dimension was significantly higher in forest and shrub than in bare land and grassland, but there was no significant difference between forest and shrub. Soil erosion resistance showed significant differences of forest > shrub > grassland > bare land. The multifractal parameters, including D0, D1, D2, ɑ(0), Δɑ(q), and Δf(q), of soil PSD have significant differences in 4 vegetation types. The generalized dimensions spectra curves of the PSD in 4 vegetation types across 5 soil layers were sigmoidal, whereas the singular spectrum function showed an asymmetric upward convex curve, indicating that the soil PSD at different depths has multifractal characteristics. Soil erosion resistance had significant relationships with multifractal parameters. This study provided an important insight for the evaluation of soil structure improvement and the effects of erosion control by vegetation restoration in frequent debris flow-affected areas.